Real Interest Rates and Inflation: An Ex-Ante Empirical Analysis. - Kandel, Shmuel; Ofer, Aharon R; Sarig, Oded (Journal of Finance, 1996)
The authors develop a method of measuring ex ante real interest rates using prices of index and nominal bonds. Employing this method and newly available data, they directly test the Fisher hypothesis that the real rate of interest is independent of inflation expectations. The authors find a negative correlation between ex ante real interest rates and expected inflation. This contradicts the Fisher hypothesis but is consistent with the theories of Robert A. Mundell and James Tobin, Michael R. Darby and Martin Feldstein, and Rene Stulz. The authors also find that nominal interest rates include an inflation risk premium that is positively related to a proxy for inflation uncertainty.